Prophylactic effects of swimming exercise on autophagy-induced muscle atrophy in diabetic rats - Lee, Youngjeon (Korean Association for Laboratory Animal Science, 2012)
Diabetes decreases skeletal muscle mass and induces atrophy. However, the mechanisms by which hyperglycemia and insulin deficiency modify muscle mass are not well defined. In this study, we evaluated the effects of swimming exercise on muscle mass and intracellular protein degradation in diabetic rats, and proposed that autophagy inhibition induced by swimming exercise serves as a hypercatabolic mechanism in the skeletal muscles of diabetic rats, supporting a notion that swimming exercise could efficiently reverse the reduced skeletal muscle mass caused by diabetes. Adult male Sprague-Dawley rats were injected intraperitoneally with streptozotocin (60 mg/kg body weight) to induce diabetes and then submitted to 1 hr per day of forced swimming exercise, 5 days per week for 4 weeks. We conducted an intraperitoneal glucose tolerance test on the animals and measured body weight, skeletal muscle mass, and protein degradation and examined the level of autophagy in the isolated extensor digitorum longus, plantaris, and soleus muscles. Body weight and muscle tissue mass were higher in the exercising diabetic rats than in control diabetic rats that remained sedentary. Compared to control rats, exercising diabetic rats had lower blood glucose levels, increased intracellular contractile protein expression, and decreased autophagic protein expression. We conclude that swimming exercise improves muscle mass in diabetes-induced skeletal muscle atrophy, suggesting the activation of autophagy in diabetes contributes to muscle atrophy through hypercatabolic metabolism and that aerobic exercise, by suppressing autophagy, may modify or reverse skeletal muscle wasting in diabetic patients.